Parâmetros Curriculares Nacionais para o Ensino de Ciências Naturais: Conhecimento e Ação Docente - Sousa, Roselene Ferreira (2012)
This research was intended to investigate if the Science teachers of elementary school know and use in their teaching activities, the directives, guidelines and objectives of the “PCN” for the teaching of Natural Sciences. The study, using a qualitative approach is descriptive in the data analysis. The Methodology was chosen as the case study and the instruments of data collection were document analysis, observation, interviews and reports from students. Initially the possibilities of research were tested with a literature review, gathering authors to the theoretical study. Following an exploratory visit was made in order to choose schools and subjects in the research, selected according to some criteria such as location of schools, school principals and teachers of receptivity, initial training and service time of the teachers. Two schools, two teachers and their students met the criteria established, and therefore has been chosen. With the insertion field, schools, teachers and students were characterized in order to identify the environment and the research subjects. At first the study, with the incursion of literature, we dealt with the repercussions of the economic, political and social development of curriculum for teaching Science, analyzing the changes in the Brazilian educational scenario, especially in the sciences, highlighting the implications for teaching and learning from an epistemological reflection. In the second moment, the curriculum was studied guidelines for the teaching and learning of science prescribed in Law 9.394/96 and “PCN” Natural Sciences, discussing the importance of using content procedural and attitudinal development classes, then to analyze current perspectives to the teaching of science subjects. Lastly was the analysis of science teaching from the teacher action research subjects, in order to perceive evidences of the use of “PCN” in the daily lessons. One can consider that the science teachers in his speech give evidence of knowing the guidelines and objectives prescribed by the “PCN”. However, in his teaching activities, it is perceived that such guidelines are presented in a very thin, making it clear that the prospect of a teaching and learning grounded in assumptions of construction of scientific knowledge, proclaimed in such curriculum guidelines, is not employed consistently, a fact explained also by students in their accounts of the Science classes. One can perceive, therefore, that despite the efforts made in developing curriculum guidelines and parameters for Science teaching, as suggestions for improving the quality of teaching of Science subjects in the country, there is a gap between the prescribed and lived in daily life classes.